Effects of perceived variety-support on middle school students’ learning engagement in physical education: the mediating role of motivation - Miao, Miao; Chai, Hongqin; Xue, Rui; Wang, Qi (Frontiers in Psychology, 2024)
High engagement in physical education (PE) could effectively develop students’ motor competence and promote physical activity, which was significantly important for students’ physical and mental health. Researches had shown that motivation was an important factor in explaining students’ learning engagement, and variety-support as the fourth independent psychological need was a potential factor influencing students’ learning motivation. However, there was a lack of empirical research evidence on the effect of perceived variety-support on middle school students’ learning engagement in PE and the influencing mechanisms. This study aimed to investigate the direct effect of perceived variety-support on learning engagement in PE and the mediating effect of motivation in PE on the relationship. A cross-sectional study was conducted and 587 middle school students from Liaoning province filled the paper-and-pencil questionnaires adopting perceived variety-support in PE scale (PVSPES), utrecht work engagement scale-student (UWES-S), and perceived locus of causality in PE scale, which had been proved to have good reliability and validity (294 boys and 293 girls, Mage=13.47 ± 0.94). The results showed three variables were significantly positively correlated with each other (r=0.323-0.562 p<0.01) and perceived variety-support in PE could not only directly promote middle school students’ learning engagement in PE but also indirectly through the mediating effect of motivation in PE. Therefore, in order to better promote students’ participation in PE class, we should pay more attention to satisfy students’ varied PE learning needs and stimulate students’ autonomous learning motivation.